Solid Pseudopapillary Neoplasm of the Pancreas with High-Grade Malignant Transformation Involving p16-RB Pathway Alterations. (13th January 2020) - Tomioka, Kodai; Ohike, Nobuyuki; Aoki, Takeshi; Enami, Yuta; Fujimori, Akira; Koizumi, Tomotake; Kusano, Tomokazu; Nogaki, Koji; Tashiro, Yoshihiko; Wada, Yusuke; Hakozaki, Tomoki; Shibata, Hideki; et al.
Abstract : Solid pseudopapillary neoplasm (SPN) of the pancreas has generally been regarded as a low-grade malignant tumour that preferentially develops in young women and can have a good prognosis with surgery. Among the few patients who have died from metastatic SPN are mostly those whose tumours harbour an undifferentiated component characterized by diffuse sheets of cells with increased nuclear atypia and proliferative index. We herein report a case of an aggressive, fatal, solid pseudopapillary neoplasm (SPN) of the pancreas in a 63-year-old woman complaining of epigastric pain. Despite having undergone surgical resection for a 10 cm pancreatic mass and multiple liver metastases, the patient later died due to uncontrollable metastases 36 months after the initial surgery. Histological examination showed that the tumour displayed unusual high-grade malignant features, showing diffuse sheets of cells with increased nuclear atypia and proliferative activity, along with conventional low-grade malignant features. The tumour was subsequently recognized as an SPN with foci of high-grade malignant transformation according to the 2010 World Health Organization classification. Immunohistochemical studies revealed that p16-RB pathway alterations contributed to the high-grade malignant transformation. The present case report suggests the necessity for developing diagnostic and treatment methods targeting p16 and RB for high-grade variants of SPN.